2013
DOI: 10.1590/s2236-89062013000400011
|View full text |Cite
|
Sign up to set email alerts
|

Flora polínica da reserva do Parque Estadual das Fontes do Ipiranga(São Paulo, Brasil) Família: 54-Passifloraceae

Abstract: -(Pollen flora of Reserva do Parque Estadual das Fontes do Ipiranga (São Paulo, Brasil). Family: 54-Passifloraceae). Pollen grains of 11 species of Passifloraceae, belonging to the genus Passiflora L. (Passiflora alata Curtis, P. cincinnata Mast., P. edulis Sims, P. haematostigma Mart. ex Mast., P. jilekii Wawra, P. miersii Mast., P. morifolia Mast., P. porophylla Vell., P. sidaefolia M. Roemer, P. truncata Regel e P. villosa Vell.), ocurring in the Reserva do Parque Estadual das Fontes do Ipiranga were studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…Results in the current study do not meet those found by Presting (1965), since he considered the presence of 4-colpi in the first species and colpus aperture type in the second specie. Presting (1965) described P. mediterranea aperture as 12-colpate; and Verdasca et al (2013), as 6-syncolpate or 8 (10-12) pantocolporate, whereas the current study considered the aperture as 6-12-colporate.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Results in the current study do not meet those found by Presting (1965), since he considered the presence of 4-colpi in the first species and colpus aperture type in the second specie. Presting (1965) described P. mediterranea aperture as 12-colpate; and Verdasca et al (2013), as 6-syncolpate or 8 (10-12) pantocolporate, whereas the current study considered the aperture as 6-12-colporate.…”
Section: Discussionmentioning
confidence: 78%
“…Spirlet (1965) used pollen data to help taxonomic classification. Later studies such as those by García et al (2002), Araújo & Santos (2004), Milward-de-Azevedo et al (20042010), Barrios et al (2005), Dettke & Santos (2009), Evaldt et al (2011), Tangarife et al (2011), Mezzonato-Pires (2013 and Verdasca et al (2013) also helped improving the palynological knowledge on the Passifloraceae s.s. family.…”
mentioning
confidence: 98%
“…Studies dealing with the pollen morphology of Brazilian species of Passifloraceae have evidenced their apertural diversity and provided important contributions to describing pollen morphology of the family. They also highlighted problems found in the interpretations of structures and nomenclature (Carreira 1977;Roubik & Moreno 1991;Palacios-Chávez 1991;Melhem et al 2003;Milward-de-Azevedo et al 2004;2010;2014;Dettke & Santos 2009;Evaldt et al 2011;Verdasca et al 2013;Mezzonato-Pires et al 2015a;b;2018;Borges & Milward-de-Azevedo 2017;Soares et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Passifloraceae mostra-se uma família muito diversa do ponto de vista palinológico. Palinologicamente, começou a ter seus grãos de pólen estudados no decorrer do século XIX (Mohl, 1834;Fritzsche, 1837;Fischer, 1890), sendo posteriormente analisados por diversos outros autores (Erdtman, 1952;Presting, 1965;Spirlet, 1965;Huynh, 1972;Roubik;Moreno, 1991;Carreira, 1977;Amela-García et al, 2002;Melhem et al, 2003;Santos, 2004;Barrios et al, 2005;Milward-de-Azevedo et al, 2004, 2010, 2014Dettke;Santos, 2009;Evaldt et al, 2011;Verdasca et al, 2013;Borges;Mezzonato-Pires et al, 2015Soares et al, 2018;Araújo et al, 2019). Todos são unânimes ao descrever os grãos de pólen da família com grande variabilidade de características, especialmente os do gênero Passiflora, destacando a importância do entendimento apertural para a interpretação morfopolínica das espécies.…”
Section: Introductionunclassified